Study of dogania subplana aclimatization in the turtle learning center university of bengkulu - Marliansa, Meiredo; Karyadi, Bhakti; Parlindungan, Deni; Ruyani, Aceng; Nursa'adah, Euis (JPBIO (Jurnal Pendidikan Biologi), 2025)
The forest softshell turtle (Dogania subplana) is a species increasingly threatened by habitat destruction and overexploitation. This study aims to identify the acclimatization process of D. subplana in an artificial environment, specifically, an aquarium at the Turtle Learning Center (TLC). The research was conducted over 30 days from July to August 2024. Observations were made on daily behavior, body temperature, and health condition, individual biometric measurements, and environmental (abiotic) parameters. The results showed that daily behaviors such as feeding, basking, and hiding occurred regularly, indicating the species' ability to adapt to a new environment. The turtles experienced an increase in body weight, while growth in carapace length and width was very slow. The body temperature of D. subplana varied in accordance with the surrounding environmental temperature, reflecting its dependence on ambient conditions. Some individuals experienced minor health issues, such as fungal infections, but the majority remained active and healthy. Environmental factors such as temperature, humidity, pH, dissolved oxygen, total dissolved solids, and light intensity were within ranges conducive to acclimatization. These findings suggest that the aquarium at the TLC is quite effective as an ex situ conservation facility in supporting the adaptation process of D. subplana  outside its natural habitat.